A Mediating Effect of Tourist Satisfaction on The Relationship Between Sustainability Tourism and Loyalty in The Tourism Villages - Wahyuningsih, Tri; Sentosa, Ilham; Rani, Nazatul Shima binti Abdul (Research Collaboration Community (RCC), 2024)
The Sustainable Development Goals (SDGs) in the tourism sector can be achieved through a comprehensive and integrated approach considering sustainable development's economic, social, and environmental dimensions. This research aims to analyze the influence of the dimensions of sustainability on tourist loyalty in tourism villages, with tourist satisfaction as a mediating variable. This study uses a quantitative approach. The number of samples used in this research was 394 tourists from tourism villages in Karanganyar Regency, Indonesia. The data analysis method uses PLS-SEM. The analysis findings indicate that economic, environmental, and institutional sustainability have a positive and significant impact on tourist satisfaction in the tourism village of Karanganyar Regency. Tourist satisfaction has favorably and considerably influenced tourist loyalty in the tourism village of Karanganyar Regency. Tourist satisfaction positively and significantly influences the relationship between economic sustainability, environmental sustainability, and institutional sustainability with tourist loyalty in the tourism village of Karanganyar Regency. Additionally, satisfaction partially mediates the relationship between economic, environmental, and institutional sustainability with tourist loyalty. This research develops a sustainability model for tourist villages that are increasingly developing worldwide. It can be used as a strategy or reference for tourist village managers to develop sustainable tourist villages.